Mercury removal in wastewater by iron oxide nanoparticles (2016)
ABSTRACT: Mercury is one of the persistent pollutants in wastewater; it is becoming a severe environmental and public health problem, this is why nowadays its removal is an obligation. Iron oxide nanoparticles are receiving much attention due to their properties, such as: great biocompatibility, ease of separation, high relation of surface-area to volume, surface modifiability, reusability, excellent magnetic properties and relative low cost. In this experiment, Fe3O4 and γ-Fe2O3 nanoparticles were synthesized using iron salts and NaOH as precipitation agents, and Aloe Vera as stabilizing agent; then these nanoparticles were characterized by three different measurements: first, using a Zetasizer Nano ZS for their size estimation, secondly UV−visible spectroscopy which showed the existence of resonance of plasmon at λmax~360 nm, and lastly by Scanning Electron Microscopy (SEM) to determine nanoparticles form. The results of this characterization showed that the obtained Iron oxides nanoparticles have a narrow size distribution (∼100nm). Mercury removal of 70% approximately was confirmed by atomic absorption spectroscopy measurements.